Analisis Kebutuhan Pengembangan Media Pembelajaran Matematika Menggunakan Google Forms Materi Limit Fungsi Aljabar - Neni Rifatul Afiah; Heni Pujiastuti; Hepsi Nindiasari (TIRTAMATH: Jurnal Penelitian dan Pengajaran Matematika, 2021)
The objective of this research was to describe the needs analysis result of the development of learning media using Google Forms to facilitate the learning process during online learning on algebraic function limit material. The method of the research was a qualitative descriptive. The needs analysis refers to the problems faced by students during online learning. The subjects of this research were 30 students of senor high school and 5 mathematics teachers. The data collecting techniques in this research were questionnaires and interviews. The results of the research showed that learning media for mathematics using Google Forms is needed as a learning media that were attractive, effective, independent and efficient to improve the understanding of algebraic functions limits course.